Analysis of Projection Effects in OSIRIS‐REx Spectral Mapping Methods: Recommended Protocols for Facet‐Based Mapping. Issue 3 (11th March 2021) - Ferrone, Salvatore M.; Clark, Beth E.; Hawley, C. Luke; Joseph, Jonathan; Nolan, Michael C.; Bennett, Carina; Zou, Xiao‐Duan; Selznick, Sanford; Loveridge, Micheal; Deshapriya, Prasanna; Lauretta, Dante S.
Abstract: We searched for an optimized protocol for mapping observations from a point spectrometer onto a shape model composed of triangular facets, in the context of NASA's asteroid sample return mission, OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security‐Regolith Explorer). Our study was conducted before the spacecraft arrived at the mission target asteroid (101955) Bennu, and we used observational sequence plans of the OSIRIS‐REx Visible and InfraRed Spectrometer (OVIRS). We explored six methods of mapping data to shape model facets, using three spatial resolutions. We attempted to boost map fidelity by increasing the observational coverage of the surface. We find that increasing shape model resolution improves mapping quality. However, once the shape model's mean facet edge length is smaller than two‐fifths of the diameter of the instrument's field of view (FOV), the increase in quality tapers off. The six mapping methods can be broken into two categories: facets that (1) select or (2) combine (average) data from observations. The quality differences between similar averaging methods (clipped average, weighted average, etc.) are insignificant. Selecting the nearest observation to a facet best preserves an enclosed outcrop's shape and signal, but averaging spots are more conservative against errors in photometric modeling. A completely enclosed outcrop border expands into the surrounding region by 0.8–1.5 radii of the instrument's FOV. Regions smaller than the instrument's FOV are present in resulting maps; however, their signal strength is reduced as a function of their size relative to the instrument FOV. Key Points: Spectral map quality is controlled by shape model facet size, boresight spot size, and method of assigning spot data to facets Shape models with facet edges smaller than 2/5 the boresight spot diameter cease to improve map fidelity Data selection algorithms perform better than data combination methods for mapping distinct outcrops